Improve Squatting Style Long Jump Ability Through Application Audio Visual Learning (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study aims to improve the ability of squatting style long jump through the application of audio-visual learning. This research includes classroom action research. The meeting in this study was designed two cycles, namely cycle I and cycle II. The subjects of the study were 30 students of grade VIII A junior high school 2 Palopo. The research method includes classroom action research on grade VIII A students of junior high school 2 Palopo, carried out in two cycles. Each cycle consists of four stages, namely planning, execution, observation and reflection. The processing of students’ long jump ability scores in this study was measured in psychomotor, cognitive and affective domains. Based on the research that has been done, it can be concluded that the application of audio-visual learning can improve the ability to jump squat style of grade VIII A students of junior high school 2 Palopo. The results of the data analysis showed that there was a significant increase in squatting style long jump ability through the application of audio-visual learning for grade VIII A students of junior high school 2 Palopo, where in cycle I the graduation percentage of grade VIII A students of junior high school 2 Palopo was 63% and increased in cycle II with a passing percentage of 93%. In conclusion, the application of audio-visual learning can improve the squatting style long jump ability of grade VIII A students of junior high school 2 Palopo.